2005
DOI: 10.1099/mic.0.27573-0
|View full text |Cite
|
Sign up to set email alerts
|

A sulphite respiration system in the chemoheterotrophic human pathogen Campylobacter jejuni

Abstract: The ability to use sulphite as a respiratory electron donor is usually associated with free-living chemolithotrophic sulphur-oxidizing bacteria. However, this paper shows that the chemoheterotrophic human pathogen Campylobacter jejuni has the ability to respire sulphite, with oxygen uptake rates of 23±8 and 28±15 nmol O2 min−1 (mg cell protein)−1 after the addition of 0·5 mM sodium sulphite or metabisulphite, respectively, to intact cells. The C. jejuni NCTC 11168 Cj0004c and Cj0005c genes encode a monohaem cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(113 citation statements)
references
References 27 publications
(28 reference statements)
3
110
0
Order By: Relevance
“…However, this taxis navigation is most likely not mediated through transmembrane MCP-like proteins in a classical and metabolism-independent chemotaxis response, since the MCP-like proteins of this study did not mediate a detectable chemotaxis response. C. jejuni solely employs oxidative phosphorylation to generate energy (46), and this organism carries a complex and highly branched electron transport system that allows the use of a wide variety of both electron donors and acceptors (36,40). Interestingly, we observed that the attractants of C. jejuni are all electron donors, electron acceptors, or carbon sources of this bacterium, which indicates that energy taxis could be the primary driving force in environmental navigation.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…However, this taxis navigation is most likely not mediated through transmembrane MCP-like proteins in a classical and metabolism-independent chemotaxis response, since the MCP-like proteins of this study did not mediate a detectable chemotaxis response. C. jejuni solely employs oxidative phosphorylation to generate energy (46), and this organism carries a complex and highly branched electron transport system that allows the use of a wide variety of both electron donors and acceptors (36,40). Interestingly, we observed that the attractants of C. jejuni are all electron donors, electron acceptors, or carbon sources of this bacterium, which indicates that energy taxis could be the primary driving force in environmental navigation.…”
Section: Resultsmentioning
confidence: 71%
“…Interestingly, we observed that substances promoting attraction of C. jejuni NCTC11168 are all known to support the growth of C. jejuni and can be categorized as (i) metabolic substrates, including ␣-ketoglutamate, L-aspartate, L-aspargine, L-cysteine, L-glutamate, pyvuvate, and L-serine (17,34,45,48); (ii) electron donors, including formate, L-malate, Dlactate, and succinate; and (iii) electron acceptors, including fumarate, DMSO, nitrite, nitrate, and hydrogen peroxide (36,47). We observed a correlation between an attractant's potency and its efficiency as an energy source, since the preferred growth substrates L-serine and pyruvate (45) were the strongest attractants under microaerophilic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 10 ml C. jejuni culture grown with 0.08 mM P i was subjected to cellular fractionation as described by Myers & Kelly (2005).…”
Section: Methodsmentioning
confidence: 99%
“…jejuni is able to adapt to changes in environmental oxygen levels due to a complex branched electron transport system. Specifically, C. jejuni is capable of utilizing various organic or inorganic electron donors (such as formate, hydrogen, lactate, sulfite) (Myers & Kelly, 2005;Thomas et al, 2011) as well as electron acceptors such as fumarate, Trimethylamine N-oxide, DMSO, nitrite and nitrate. Under microaerobic conditions, oxygen is reduced by either a low-O 2 -affinity CioAB oxidase or by a cytochrome cb9 oxidase (Jackson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%